CREATIVE ECONOMY - EXPLORING THE CONCEPT AND EUROPEAN PERSPECTIVE - Đorić, Žarko (International Journal of Economic Practice and Policy, 2021)
In recent times, our environment and the way we produce and consume cultural goods and services are changing radically due to the strong influence of globalization, faster communication channels, global connectivity and the implementation of new information and communication technologies. In the conditions of convergence of economic, social, cultural and technological changes, the importance of strengthening creative potentials and capacities to achieve economic and other gains is very much recognized, so new development strategies are needed in this area. In such circumstances, the concept of "creative and cultural economy" is popularized worldwide as the interface between culture, economics and technology. Our world is increasingly dominated by images, sounds, symbols and ideas that create new jobs, wealth and new culture. Because of this, economic development can no longer be considered unilaterally, only through the accumulation of economic capital, but as a three-dimensional space whose dimensions are the size, structure, and the change in the relationship between economic and creative resources. In this paper, the author deals with theoretical and applied aspects of the creative economy development. The obtained results indicate a significant economic potential that the creative economy brings within the European Union, primarily in terms of employment and contribution of enterprises within the creative sector. The research aims to interpret data, describe facts, processes, and objects and empirically confirm their connections and relationships using a descriptive method and a compilation method.